Darby O'Gill and the little people [videorecording (DVD)] - Connery, Sean; Munro, Janet, 1934-1972; Sharpe, Albert; Stevenson, Robert, 1905-1986 (Walt Disney Home Video ; Distributed by Buena Vista Home Entertainment, Inc., 2004)
An old storyteller falls into a well and meets a group of leprechauns. The leprechauns give him three wishes to get his life together.